2018
DOI: 10.1002/mmce.21512
|View full text |Cite
|
Sign up to set email alerts
|

Compact four-element MIMO SIW cavity backed slot antenna with high front-to-back ratio

Abstract: In this article, a novel design of single layer, compact, multiple input multiple output (MIMO) half-mode substrate integrated waveguide (HMSIW) cavity backed quad element slot antenna with high front-to-back ratio (FTBR) is proposed. The proposed antenna consists of four rectangular SIW cavities with semi-taper radiating slots. The antenna elements are placed in a fashion to achieve high isolation. This antenna is designed for WLAN vehicular communication system to cover the frequency range of 5.84 GHz to 5.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…The lower band resonating frequency depends on the lower part of SIW cavity (below the feed point) while the upper band resonating frequency depends on upper part of SIW cavity (above the feed point) as shown in Figure . The cavity can be divided into two parts along the line aa′ as shown in Figure A and each half behaves like half‐mode SIW cavity . Each half‐mode cavity supports half of TE 220 mode.…”
Section: Antenna Design and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The lower band resonating frequency depends on the lower part of SIW cavity (below the feed point) while the upper band resonating frequency depends on upper part of SIW cavity (above the feed point) as shown in Figure . The cavity can be divided into two parts along the line aa′ as shown in Figure A and each half behaves like half‐mode SIW cavity . Each half‐mode cavity supports half of TE 220 mode.…”
Section: Antenna Design and Analysismentioning
confidence: 99%
“…But, these antennas suffer from poor performances due to bidirectional radiation characteristics. Substrate integrated waveguide (SIW) based antennas are a better substitute to provide good radiation characteristics in a planar structure. In References linearly polarized radiation in single band, dual band and triple‐band of frequencies is obtained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cavity backed slotted MIMO antenna on a square substrate of 62 × 62 mm 2 is reported that covers the 5.9 GHz frequency band with 8 dB gain in Ref. . In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, a variety of decoupling methods such as usage of polarization / pattern diversity, optimization of antenna configuration, utilization of isolating elements, and introduction of decoupling networks have been proposed to improve the isolation among antenna elements. However, these techniques will lead to high profile, large overall size, complex structure, and low radiation efficiency .…”
Section: Introductionmentioning
confidence: 99%